Appraising the stress responses in Azolla filiculoides elicited by short-term exposure of phenol - Bittu Paul (Elsevier, 2021)
Phenolic compounds comprise one of the major water pollutants. Aquatic plants are mainly affected by the toxic effects of these pollutants. In this purview, the present study attempted to study the effect of phenolic compounds on a floating fern - Azolla filiculoides, which commonly grows in stagnant water bodies. Crystalline phenol was taken as a reference compound; four different concentrations viz. 0.5, 1, 2, and 3 mM of which were applied to the plants for shorter periods of 3 and 6 days, followed by the assessment of morphological, physiological, and biochemical responses of the plants compared to the control set (0 mM). Relative growth rate, relative frond number, relative frond surface area, relative water content, chlorophyll a, and carotenoids decreased significantly with the increase in phenol concentrations and the duration of treatment. Also, the significant increase in frond necrotic area, electrolyte leakage, and malondialdehyde content exhibited the negative impacts of phenols. On the contrary, an increase in proline, total sugars, antioxidative enzymes such as superoxide dismutase, catalase, and peroxidase indicated an inherent tolerance mechanism. Moreover, H2O2 quantification, also supported by its in situ localization, presented the extent of phenol toxicity. However, contemplating the overall findings, it could be suggested that phenol-treated plants maintained their growth and physiological responses at par with the control plants, up to a concentration of 1 mM phenol.